2016
DOI: 10.1109/tip.2016.2567099
|View full text |Cite
|
Sign up to set email alerts
|

Visual Presence: Viewing Geometry Visual Information of UHD S3D Entertainment

Abstract: To maximize the presence experienced by humans, visual content has evolved to achieve a higher visual presence in a series of high definition (HD), ultra HD (UHD), 8K UHD, and 8K stereoscopic 3D (S3D). Several studies have introduced visual presence delivered from content when viewing UHD S3D from a content analysis perspective. Nevertheless, no clear definition has been presented for visual presence, and only a subjective evaluation has been relied upon. The main reason for this is that there is a limitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…It was found that involvement [31], similar to engagement [62], was highest at a viewing distance of 5.2 H (1.1 m) for 17" TVs, 3 H (1.65 m) for 42" TVs, and 2 H (1.65 m) for 65" TVs, respectively. Additionally, it was found that a viewing distance of 2.5 H (2 m) provided the highest visual presence when watching 2D images on 65" flat ultra-high-definition (UHD) TVs, followed by 0.6 H (0.5 m) and 5 H (4 m) [68]. When similar viewing conditions are considered, the current results resemble those of these studies [31,40,68].…”
Section: Effects Of Viewing Distancesupporting
confidence: 76%
See 2 more Smart Citations
“…It was found that involvement [31], similar to engagement [62], was highest at a viewing distance of 5.2 H (1.1 m) for 17" TVs, 3 H (1.65 m) for 42" TVs, and 2 H (1.65 m) for 65" TVs, respectively. Additionally, it was found that a viewing distance of 2.5 H (2 m) provided the highest visual presence when watching 2D images on 65" flat ultra-high-definition (UHD) TVs, followed by 0.6 H (0.5 m) and 5 H (4 m) [68]. When similar viewing conditions are considered, the current results resemble those of these studies [31,40,68].…”
Section: Effects Of Viewing Distancesupporting
confidence: 76%
“…Additionally, it was found that a viewing distance of 2.5 H (2 m) provided the highest visual presence when watching 2D images on 65" flat ultra-high-definition (UHD) TVs, followed by 0.6 H (0.5 m) and 5 H (4 m) [68]. When similar viewing conditions are considered, the current results resemble those of these studies [31,40,68].…”
Section: Effects Of Viewing Distancesupporting
confidence: 76%
See 1 more Smart Citation
“…viewing geometry factors (viewing distance, display resolution, display size, and display types: flat or curved). Therefore, many existing QoE studies have applied viewing geometry to design a prediction model that reflects perceptual resolution [7,[33][34][35]. Figure 2(b) geometrically depicts an example of perceived pixel according to display type.…”
Section: A) Qoe Trend On 2d Displaymentioning
confidence: 99%
“…Defocus blur as an important cue of depth perception has been widely used in image synthesis or rendering to enhance depth perception of stereoscopic 3D displays [1]- [5] and reduce the visual discomfort and fatigue [6] [7] due to mismatch between accommodation and vergence. The vergence is a depth perception process for binocular vision that brain compares and processes two images with slightly different distances from two eyes to form a single stereo image.…”
Section: Introductionmentioning
confidence: 99%